Pemasangan dan Instalasi Sistem Keamanan di Perumahan Rawan Pencuri Menggunakan CCTV Fanindo Tanjung Uncang Batam - Dija, Nur Rafia; James Siregar; Lalu Giat Juangsa Putra; Mohamad Alif Dzulfiqar; Muhammad Andi Nova; Billi Aldin Sumadireja; Yattawuri Arinta Timur (Politeknik Negeri Batam, 2025)
Criminal acts in the community such as theft of motorized vehicles, bicycles and hit-and-run victims are increasingly widespread, in the last 1 year in Fanindo housing there have been four thefts of children's bicycles. Therefore, a security system is needed in the housing to prevent and monitor things that harm the community, namely in the form of CCTV. The methods carried out in the service include surveying the location to determine the strategic installation point with the local RT head, selecting the type of camera, determining the electrical path, determining the placement of the DVR (Digital Video Recorder), and software settings. This service activity received a very positive response from both the RT management and the local community and is expected to be able to reduce criminal acts such as theft and other criminal acts.